Pursuing business opportunities in life sciences logistics in Vietnam : a case study of TNT - Chang, Meng Yi (2008)
This paper attempts to understand how TNT introduces a new service offering, the Clinical Express service, for a niche market segment, the life sciences industry, and how TNT exploits the opportunities available to launch the new service offering in a specific market, Vietnam.